2007
DOI: 10.2334/josnusd.49.241
|View full text |Cite
|
Sign up to set email alerts
|

Dentinogenesis imperfecta type II: an affected family saga

Abstract: Dentinogenesis imperfecta (DI) type II orhereditary opalescent dentin is inherited in simple autosomal dominant mode with high penetrance and low mutation rate. It generally affects both the deciduous and permanent dentitions. DI type II corresponds to a localized form of mesodermal dysplasia, observed in histodifferentiation. Early diagnosis and treatment are therefore, fundamental, aiming at obtaining a favourable prognosis since late intervention makes treatment more complex. We present two cases of DI type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…5,9 No characteristic features of osteogenesis imperfecta (i.e., multiple bone fracture, hyperextensible joint, progressive deafness) 8 and the Brandywine type of dentinogenesis imperfecta (i.e., multiple pulp exposure and shell teeth) 8 were Discussion W.C. Barrett (1882) first recognized opalescent dentin and Talbot (1893) described it as an enamel defect. 1 This condition reportedly occurs in 1 in every 8,000 births, 2,3 and is caused by a mutation in the dentin sialophospho protein gene (DSPP, 4q21.3). 2,4 The term dentinogenesis imperfecta was coined by Robert and Schour in 1939.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…5,9 No characteristic features of osteogenesis imperfecta (i.e., multiple bone fracture, hyperextensible joint, progressive deafness) 8 and the Brandywine type of dentinogenesis imperfecta (i.e., multiple pulp exposure and shell teeth) 8 were Discussion W.C. Barrett (1882) first recognized opalescent dentin and Talbot (1893) described it as an enamel defect. 1 This condition reportedly occurs in 1 in every 8,000 births, 2,3 and is caused by a mutation in the dentin sialophospho protein gene (DSPP, 4q21.3). 2,4 The term dentinogenesis imperfecta was coined by Robert and Schour in 1939.…”
Section: Case Reportmentioning
confidence: 99%
“…1 This condition reportedly occurs in 1 in every 8,000 births, 2,3 and is caused by a mutation in the dentin sialophospho protein gene (DSPP, 4q21.3). 2,4 The term dentinogenesis imperfecta was coined by Robert and Schour in 1939. 2,5 Witkop and Rao 6 in 1971 suggested that the term hereditary opalescent dentin should be used for isolated traits and the term dentinogenesis imperfecta (DI) be used for conditions associated with osteogenesis imperfecta.…”
Section: Case Reportmentioning
confidence: 99%
“…1 Robert and Schour coined the term “DI” in 1939. 2 Skillen, Finn, and Hodges coined the term “hereditary opalescent dentin.” 1 …”
Section: Introductionmentioning
confidence: 99%
“…Dentinogenesis imperfecta (DI) was probably first recognized by Barret in 1882 5. The term was coined by Robert and Schor in 1939 4.…”
Section: Introductionmentioning
confidence: 99%